ANALISIS KOMPARATIF RASIO KEUANGAN ANTARA PT HM SAMPOERNA,TBK & PT GUDANG GARAM,TBK - Erbina Meliana Purba; Lisa Marlina (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT   The purpose of this research is to analyze the differences and to compare financial performance between financial performance of PT HM  Sampoerna,Tbk and P.T Gudang Garam,Tbk. The data used are the annual financial statements of PT HM. Sampoerna,Tbk and PT Gudang Garam,Tbk, which have been audited from 2009-2011.This research is case study research. The method of data analysis is descriptive analysis. The analysis technique used is comparison of financial Ratios with the combined ratio analysis and statistical technique using Mann-Whitney (U-Test), with a significance level (α) = 5%. Analyzing data using statistical data processed by software SPSS for windows 16.0. The results showed that the financial performance of PT HM Sampoerna,Tbk better than PT Gudang Garam,Tbk. The Financial Performance is measured by liquidity, leverage, activity and profitability ratios. According to the result of Mann-Whitney (U-Test )method, conclude that there is a different of financial performance between PT HM Sampoerna,Tbk and PT Gudang Garam,Tbk comprehensively. Financial performance of PT HM. Sampoerna,Tbk better than PT Gudang Garam, Tbk. The hypothesis testing for 11 financial ratios both of them, show that 10 ratios are different significantly namely CR, QR, DAR, DER, ITO, TATO, NPM, ROI, ROE, TIE. Another ratio namely: EPS doesn’t show the significant difference. Key Words : Current Ratio, Quick Ratio, DAR, DER, TIE, Inventory Turnover Ratio, TATO, NPM, ROE, ROI, EPS.